الأخطاء الشائعة في الكتابة لدى دارسي العربية بوصفها لغة أجنبية في ماليزيا والحلول المقترحة- دراسة لسانية تطبيقية - Chtaibi, Khalid; Abd Hamid, Mohd Azrul Azlen; Iisiaq Nasirudeen, Abdulwasiu (Al-Madinah International University, 2024)

(untitled)
This linguistic study aims to identify and analyse the common errors in the writings of students of the Department of Arabic Language at the Kulliyah of Languages and Management in the International Islamic University Malaysia (IIUM), at the levels morphological and grammatical. It examines the errors of a sample of the assignments of students in the bachelor degree stage, describing, correcting them and clarifying the skills of their treatment to be an educational reference for all students of Arabic as a foreign language, not only in Malaysia but all over the world. The researcher is using the descriptive and analytical medothology, where the study identifies the common errors that students fall into, and formulates a reference course that reviews the most prominent of these errors and methods of treatment to avoid them in the future. The study concluded the following results: 1- The mother tongue (Malaysian) has an impact in making such mistakes but it is not the sole cause; 2-: Weakness of educational programs and lack of parallel educational activities that provide the appropriate linguistic environment for practicing the Arabic language and training to enhance its skills, especially writing; 3-: The absence of practical references useful in identifying and correcting errors, compared to English language. The research comes out with a set of conclusions and recommendations to be submitted to all concerned institutions and parties in order to bridge the gap and fix the imbalance in this regard.